A method for preparing imitation glazed aluminum alloy curtain wall panel
The opaque enamel glaze layer is formed through the porcelain anodization process, which solves the corrosion resistance of curtain wall materials under wind, sun and rain, and at the same time achieves a decorative effect comparable to that of porcelain glaze, providing high hardness, wear resistance and Stability, meets the corrosion resistance and decorative needs of curtain wall panels.
Patent Information
- Application Number
- CN202211714712.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The prior art is difficult to achieve both good corrosion resistance and excellent decorative effects in curtain wall materials, especially when curtain wall components are affected by adverse factors such as wind, sun and rain during long-term use, they are prone to corrosion and damage, and It is difficult to inspect and maintain the adapter system in concealed parts regularly.
The aluminum alloy curtain wall panel is processed by ceramic anodizing process, and the electrolyte composed of chromium potassium oxalate, chromic anhydride, citric acid, etc. is anodic oxalate to form an opaque enamel glaze layer, combining the sealing and drying and aging steps. Improve the corrosion resistance and decorative properties of the oxide film.
A high hardness, wear resistance, good thermal insulation and electrical insulation atmospheric glaze surface has strong corrosion resistance and is comparable to that of porcelain glaze. The opaque film layer has low requirements for surface processing of aluminum profiles, is easy to clean, and has stable Better than other anodized films.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy processing, and in particular relates to a method for preparing an imitation glaze aluminum alloy curtain wall panel. Background Art
[0002] With the rapid development of the country's current economy and the continuous improvement of people's living standards, contemporary architecture increasingly advocates the development of new architectural aesthetics and requires the creation of new architectural art aesthetics. Because the curtain wall of a super-high-rise building can better reflect the modern aesthetics of the building, it can meet people's demand for the multi-function of the modern building curtain wall. Most of the keels and connection systems of the building curtain wall are made of metal materials. During long-term use, they are easily corroded and damaged due to factors such as time, space, and environment. The curtain wall components are subjected to long-term stress, especially the adapter system, which is usually located in a hidden part of the building curtain wall and cannot be regularly inspected and maintained. Once damaged or failed, it will cause great harm. On February 18, 2022, Chinese patent CN202111267058.9 disclosed a method for preparing an unfired glazed aluminum alloy curtain wall panel. The disclosed unfired glazed aluminum alloy curtain wall panel is non-toxic, odorless, energy-saving and environmentally friendly, and has high density. The unfired glazed aluminum curtain wall panel is electrostatically sprayed with glaze on the surface of the aluminum curtain wall panel to form a glazed unfired glazed aluminum curtain wall panel. Among the many anti-corrosion methods, it is very difficult to properly and reasonably select a suitable anti-corrosion method. The curtain wall is on the outer surface of the building. During its entire life cycle, it is often damaged by various adverse factors such as wind, sun, rain, etc. Therefore, the components of the curtain wall are required to have sufficient corrosion resistance and safety, so the curtain wall materials must have good corrosion resistance or excellent corrosion resistance treatment. At the current stage of economic and technological development, the purpose of building curtain wall corrosion is to ensure structural safety, make full use of the mechanical properties of the material, and achieve the common development of safety and economic benefits. The basic function of curtain wall structure corrosion prevention is to save resources, use resources rationally, and improve resource utilization. It also plays an important role in the safety of the curtain wall. Technical personnel in this field are in urgent need of developing a preparation method for imitation glazed aluminum alloy curtain wall panels to meet existing usage needs and performance requirements. Summary of the invention
[0003] The purpose of the invention is to provide a method for preparing an imitation glazed aluminum alloy curtain wall panel in view of the existing problems.
[0004] A method for preparing an imitation glaze aluminum alloy curtain wall panel, after the aluminum alloy plate is subjected to the pretreatment steps of alkaline degreasing, hot water cleaning, cold water cleaning, chemical polishing, and cold water cleaning, the method further comprises the following steps: (1) porcelain anodizing: placing the aluminum alloy plate as an anode in an electrolyte, applying power to perform porcelain anodizing, and obtaining a porcelain anodized aluminum alloy plate, wherein the electrolyte is 35-40 g / L potassium chromium oxalate, 6-8 g / L chromic anhydride, 1-1.2 g / L citric acid, and 7.2-9 g / L oxalic acid, first dissolving potassium chromium oxalate in distilled water at 50-60°C, pouring the solution into a tank, then adding oxalic acid, chromic anhydride, and citric acid, and then adding distilled water to the working liquid surface, stirring evenly, and adjusting the pH value to 1.8-2.0 with dilute sulfuric acid to obtain an electrolyte;
[0005] Porcelain anodizing is the process of obtaining a smooth, enamel-like, opaque oxide film on the polished surface of aluminum alloys, especially hard aluminum.
[0006] (2) Cleaning and sealing: Clean the surface of the porcelain anodized aluminum alloy plate with distilled water, and immerse the cleaned porcelain anodized aluminum alloy plate in 90-95°C fatty acid for sealing for 10-20 minutes;
[0007] The physical or chemical treatment process of the oxide film after anodizing of aluminum alloy is sealing, which reduces the porosity and adsorption capacity of the oxide film so as to seal the dye in the micropores and improve the corrosion resistance and wear resistance of the film.
[0008] (3) Drying and aging: After drying, aging is carried out. Aging is carried out by placing the sealed product in an environment with a temperature of 20°C and a relative humidity of 50% for 100 to 120 hours or soaking it in 70°C pure water for 10 to 15 minutes after the sealed product is obtained.
[0009] Furthermore, in step (3), the drying is performed at 50-60° C. for 0.5-1 h.
[0010] Furthermore, the fatty acid in step (2) is oleic acid or stearic acid.
[0011] Stearic acid is a weak organic acid that can react with alkali to form stearate. Oleic acid is a colorless oily liquid, an unsaturated fatty acid.
[0012] Furthermore, in step (1), the ceramic anodizing current density is 1.0 to 3 A / dm 2 , voltage 115~125V, time 30~40min, temperature 55~60℃.
[0013] Furthermore, the aluminum alloy plate is one of 1100 aluminum alloy plate, 6063 aluminum alloy plate, and 6061 aluminum alloy plate.
[0014] Furthermore, the mass fraction of the dilute sulfuric acid in step (1) is 8% to 10%.
[0015] Beneficial effects of the present invention:
[0016] The invention discloses a method for preparing an imitation glaze aluminum alloy curtain wall panel. The oxide film obtained by porcelain anodizing is light gray and opaque, and its appearance is similar to that of a porcelain enamel layer, and is also called imitation glaze anodizing. The film layer is dense, has high hardness, wear resistance, good thermal insulation and electrical insulation, wherein oxalic acid promotes film growth. Chromic anhydride affects the conductivity of the solution, the speed of forming the anodized film, and the color of the anodized film. The ceramic-like opaque film is mainly the result of the action of potassium chromium oxalate and chromic anhydride. Within the range of anodizing process conditions, the imitation porcelain effect is good, and the anodized film is transformed into an opaque gray force. The composition of potassium chromium oxalate is simple, and the operating voltage and working temperature are low. A high-quality porcelain oxide film can be obtained by combining oxalic acid, chromic anhydride, citric acid, and potassium chromium oxalate, and it is easy to operate in production.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] The invention discloses a method for preparing an imitation glazed aluminum alloy curtain wall panel. After porcelain anodization, the oxide film is opaque, and the appearance is similar to porcelain glaze and enamel, and the panel has high hardness and wear resistance, good thermal insulation and electrical insulation, and its corrosion resistance is higher than that of the sulfuric acid method, and the panel has good decorative effect. The porcelain anodized film has high hardness and strong corrosion resistance, and its decorative effect is comparable to that of porcelain glaze. Moreover, since the oxide film is opaque, the requirements for machining the surface of the aluminum profile are not high, and the anti-glaze effect is good. The imitation glazed aluminum alloy curtain wall panel has a unique decorative effect that cannot be matched by other anodized films, and the panel does not fade, is easy to clean, and has good stability and decorativeness. DETAILED DESCRIPTION
[0019] The present invention is described below with specific examples, but is not intended to be limiting of the present invention.
[0020] Example 1
[0021] A QC12Y CNC shearing machine was used to process a 6063 aluminum alloy plate with a length of 1000 mm, a width of 1000 mm, and a thickness of 1.5 mm. The processed aluminum alloy plate was subjected to alkaline degreasing, 75°C hot water cleaning, 25°C cold water cleaning, chemical polishing, and 25°C cold water cleaning pretreatment steps. Alkaline degreasing: the alkaline degreasing solution contained 50 g / L sodium tripolyphosphate, 1 g / L sodium hydroxide, and 30 g / L sodium silicate, the temperature was 55°C, and the immersion time was 1.5 min; chemical polishing: 450 g / L sodium hydroxide, 450 g / L sodium nitrate, 250 g / L sodium nitrite, 100 g / L sodium tripolyphosphate, the temperature was 105°C, and the time was 605 s. The following steps are also included: (1) Ceramic anodizing: the aluminum alloy plate is placed in the electrolyte as the anode, and power is applied for ceramic anodizing, with a current density of 2 A / dm 2 , voltage 120V, time 35min, temperature 58℃, to obtain a porcelain anodized aluminum alloy plate, wherein the electrolyte is 35g / L potassium chromium oxalate, 7g / L chromic anhydride, 1.1g / L citric acid, 7.5g / L oxalic acid, first dissolve potassium chromium oxalate in 55℃ distilled water, pour into the tank, then add oxalic acid, chromic anhydride, citric acid, and then add distilled water to the working liquid surface, stir evenly, adjust the pH value to 1.9 with dilute sulfuric acid, and obtain an electrolyte, the mass fraction of dilute sulfuric acid is 9%; ( 2) Cleaning and sealing: Clean the surface of the porcelain anodized aluminum alloy plate with distilled water, immerse the cleaned porcelain anodized aluminum alloy plate in 90℃ stearic acid for sealing for 20 minutes, and after sealing, rinse it twice with water, hang it in the drip drying area to drip dry, and use exhaust fans while dripping; (3) Drying and aging: Drying is to place it at 55℃ for 0.75h, and then hang the dried plate into the lower row area. Move it gently when transferring it, and do not let the rack swing too much to avoid damaging the plate. When placing it in the lower row, handle it gently and place it neatly on a special material transport vehicle. The distance between the plates is 5mm, and the height is 10 layers. After drying, ageing is carried out. Aging is to place it in an environment with a temperature of 20℃ and a relative humidity of 50% for 100h after sealing.
[0022] Product: The average thickness of the oxide film is 20μm, the sealing treatment has a uniform and continuous appearance, there is no peeling, sand holes, powdering areas, no marks and slight water stains, the color change degree is level 1, the salt spray corrosion resistance is level 9, and the wear resistance is 348g / μm.
[0023] Example 2
[0024] Preparation method of imitation glazed aluminum alloy curtain wall panel: use QC12Y CNC shearing machine to process 1100 aluminum alloy plate with length of 500mm, width of 1000mm and thickness of 1mm, and then process the processed aluminum alloy plate through alkaline degreasing, 75℃ hot water cleaning, 25℃ cold water cleaning, chemical polishing and 25℃ cold water cleaning pretreatment steps, wherein alkaline degreasing: alkaline degreasing liquid contains 50g / L sodium tripolyphosphate, 1g / L sodium hydroxide, 30g / L sodium silicate, temperature is 50℃, and soaking time is 1min; chemical polishing: sodium hydroxide 450g / L, sodium nitrate 450g / L, sodium nitrite 250g / L, sodium tripolyphosphate 100g / L, temperature 100℃, time 60-70s. It also includes the following steps: (1) porcelain anodizing: place the aluminum alloy plate as the anode in the electrolyte, and conduct porcelain anodizing by powering on, with a current density of 1.0A / dm 2 , voltage 115V, time 30min, temperature 55℃, to obtain a porcelain anodized aluminum alloy plate, wherein the electrolyte is 35g / L potassium chromium oxalate, 8g / L chromic anhydride, 1.2g / L citric acid, and 9g / L oxalic acid. First, dissolve potassium chromium oxalate in 50℃ distilled water, pour it into the tank, then add oxalic acid, chromic anhydride, citric acid, and then add distilled water to the working liquid surface, stir evenly, adjust the pH value to 2.0 with dilute sulfuric acid, and obtain the electrolyte, the mass fraction of dilute sulfuric acid is 10%; ( 2) Cleaning and sealing: Clean the surface of the porcelain anodized aluminum alloy plate with distilled water, immerse the cleaned porcelain anodized aluminum alloy plate in 95℃ stearic acid for sealing for 20 minutes, and after sealing, rinse it twice with water, and then hang it in the drip-drying area to drip dry. Use an exhaust fan while dripping dry; (3) Drying and aging: Drying is to place it at 50℃ for 0.5h, and then hang the dried plate into the lower row area. Move it gently when transferring it, and do not let the rack swing too much to avoid damaging the plate. When placing it in the lower row, handle it gently and place it neatly on a special material transport vehicle. The distance between the plates is 5mm, and the height is 10 layers. After drying, age it. Aging is to soak it in 70℃ pure water for 10 minutes after sealing.
[0025] Product: The average thickness of the oxide film is 22μm, the sealing treatment has a uniform and continuous appearance, there is no peeling, sand holes, powdering areas, no marks and slight water stains, the discoloration level is 1, the salt spray corrosion resistance is 9, and the wear resistance is 339g / μm.
[0026] Example 3
[0027] A method for preparing an imitation glazed aluminum alloy curtain wall panel,
[0028] The first step, degreasing and cleaning: QC12Y CNC shearing machine is used to process 6010 aluminum alloy plates with a length of 1000mm, a width of 1000mm and a thickness of 2mm. Before micro-arc oxidation treatment, 400#, 600#, 800#, 1000# and 1200# water sandpaper are used to grind the workpiece step by step. The clamped 6010 aluminum alloy plate is placed in a 40KHz800W ultrasonic cleaning tank for cleaning for 30 minutes. The surface is 100mm away from the liquid level of the cleaning liquid. Alkaline degreasing: alkaline degreasing liquid contains 50g / L sodium tripolyphosphate, 1g / L sodium hydroxide, 30g / L sodium silicate, the temperature is 60℃, and the immersion time is 2min; chemical polishing: sodium hydroxide 450g / L, sodium nitrate 450g / L, sodium nitrite 250g / L, sodium tripolyphosphate 100g / L, temperature 110℃, time 70s. After the processed aluminum alloy plate is subjected to the pretreatment steps of alkaline degreasing, 75°C hot water cleaning, 25°C cold water cleaning, chemical polishing, and 25°C cold water cleaning, the following steps are also included: (1) porcelain anodizing: placing the aluminum alloy plate as an anode in an electrolyte and applying electricity for porcelain anodizing at a current density of 3A / dm 2 , voltage 125V, time 40min, temperature 60℃, to obtain a porcelain anodized aluminum alloy plate, wherein the electrolyte is 40g / L potassium chromium oxalate, 8g / L chromic anhydride, 1.2g / L citric acid, 9g / L oxalic acid, first dissolve potassium chromium oxalate in 60℃ distilled water, pour into the tank, then add oxalic acid, chromic anhydride, citric acid, and then add distilled water to the working liquid surface, stir evenly, adjust the pH value to 2.0 with dilute sulfuric acid, and obtain an electrolyte, the mass fraction of dilute sulfuric acid is 10%; (2) Cleaning and sealing: Clean the surface of the porcelain anodized aluminum alloy plate with distilled water, immerse the cleaned porcelain anodized aluminum alloy plate in 95℃ stearic acid for sealing for 20 minutes, and after sealing, rinse it twice with water, hang it in the drip drying area to drip dry, and use exhaust fans while dripping; (3) Drying and aging: Drying is to place it at 60℃ for 1 hour, and then hang the dried plate into the lower row area. Move it gently when transferring it, and do not let the rack swing too much to avoid damaging the plate. When placing it in the lower row, handle it gently and place it neatly on a special material transport vehicle. The distance between the plates is 5mm, and the height is 10 layers. After drying, age it. Aging is to place it in an environment with a temperature of 20℃ and a relative humidity of 50% for 120 hours after sealing.
[0029] Product: The average thickness of the oxide film is 21μm, the sealing treatment has a uniform and continuous appearance, there is no peeling, sand holes, powdering areas, no marks and slight water stains, the discoloration level is 1, the salt spray corrosion resistance is 9, and the wear resistance is 345g / μm.
[0030] Note: The salt spray corrosion resistance test is carried out in accordance with the provisions of GB / T12967.3 Aluminum and aluminum alloy anodic oxide film test method Part 3: Copper accelerated acetic acid salt spray test (CASS test). The weather resistance test is carried out in accordance with the provisions of GB / T12967.4 Aluminum and aluminum alloy anodic oxide film test method - Part 4: Determination of ultraviolet resistance of colored anodic oxide film. The wear resistance test is carried out in accordance with the provisions of GB / T12967:7-2010 Aluminum and aluminum alloy anodic oxide film test method Part 7: Determination of wear resistance of anodic oxide film using falling sand tester.
[0031] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an imitation glazed aluminum alloy curtain wall panel, wherein the aluminum alloy panel is subjected to the pre-treatment steps of alkaline degreasing, hot water cleaning, cold water cleaning, chemical polishing, and cold water cleaning, characterized in that: The method also includes the following steps: (1) porcelain anodizing: placing an aluminum alloy plate as an anode in an electrolyte, applying power to perform porcelain anodizing, and obtaining a porcelain anodized aluminum alloy plate, wherein the electrolyte is 35-40 g / L potassium chromium oxalate, 6-8 g / L chromic anhydride, 1-1.2 g / L citric acid, and 7.2-9 g / L oxalic acid. First, dissolve potassium chromium oxalate in distilled water at 50-60°C, pour into a tank, then add oxalic acid, chromic anhydride, and citric acid, and then add distilled water to the working liquid surface, stir evenly, and adjust the pH value to 1.8-2.0 with dilute sulfuric acid to obtain an electrolyte. The current density of porcelain anodizing is 1.0-3 A / dm 2 , voltage 115~125V, time 30~40min, temperature 55~60℃; (2) Cleaning and sealing: clean the surface of the porcelain anodized aluminum alloy plate with distilled water, and immerse the cleaned porcelain anodized aluminum alloy plate in 90~95℃ fatty acid for sealing for 10~20min; (3) Drying and aging: after drying, aging is carried out. Aging is to place the plate in an environment with a temperature of 20℃ and a relative humidity of 50% for 100~120h after sealing treatment, or soak it in 70℃ pure water for 10~15 minutes after sealing treatment.
2. The method for preparing an imitation glazed aluminum alloy curtain wall panel according to claim 1, characterized in that: The drying in step (3) is performed at 50-60° C. for 0.5-1 h.
3. The method for preparing an imitation glazed aluminum alloy curtain wall panel according to claim 1, characterized in that: In step (2), the fatty acid is oleic acid or stearic acid.
4. The method for preparing an imitation glazed aluminum alloy curtain wall panel according to claim 1, characterized in that: The aluminum alloy plate is one of 1100 aluminum alloy plate, 6063 aluminum alloy plate and 6061 aluminum alloy plate.
5. The method for preparing an imitation glazed aluminum alloy curtain wall panel according to claim 1, characterized in that: The mass fraction of dilute sulfuric acid in step (1) is 8% to 10%.
Citation Information
Patent Citations
Preparation method of unfired glazed aluminum alloy curtain wall plate
CN114054323A
Porcelain oxidation method of aluminum piece
CN102312263A
Formation of a polychromatic motif by electrolytic coloration of a preanodised aluminium or aluminium alloy article
GB1405872A